A small bowel perforation in a goalkeeper: a case report and return-to-play progression - Johnston, K.; Condon, T. A.; Ciocca, M.; Aguilar, A. (Journal of Athletic Training, 2021)
Sport-related intra-abdominal injuries are rare and may be associated with significant morbidity if missed. We present the case of a 21-year-old male collegiate goalkeeper who sustained a small bowel perforation after colliding with a teammate in practice. The athlete underwent laparoscopic primary repair of his small bowel perforation, a relatively uncommon type of surgical intervention for this injury given that similar patients are typically treated via laparotomy. Due to the rarity of small intestine injuries in athletes, information regarding the success of surgical interventions and return-to-play (RTP) standards is lacking, as is information on outcomes and return to sport after a laparoscopic repair. In this case report, we discuss the unique challenge of constructing an RTP protocol for this high-level athlete and propose a protocol for RTP after an intra-abdominal injury treated laparoscopically.